Vitamin K deficiency bleeding in Great Britain and Ireland: British Paediatric Surveillance Unit Surveys, 1993–94 and 2001–02. Issue 9 (30th May 2007) - McNinch, Andrew; Busfield, Alison; Tripp, John
Abstract : Objective: To conduct and report monitoring of vitamin K deficiency bleeding (VKDB) in Great Britain and Ireland following the 1988–90 survey (VKDB-90). Design: Two 2-year surveys conducted during 1993–4 (VKDB-94) and 2001–02 (VKDB-02). Setting: Data collected from all consultant paediatricians in Great Britain and Ireland. Patients: All infants presenting with bleeding resulting from vitamin K (VK) deficiency. Main outcome measures: Incidence of VKDB, related mortality/morbidity and VK prophylaxis recommended/received, noting predisposing features. Results: Compared with previous studies, VKDB-02 found fewer cases of VKDB (RR: 0.27 (95% CI: 0.12 to 0.59), p<0.001) with no deaths, no long-term morbidity and reduced incidence among those receiving any oral dosing (RR: 0.24 (95% CI: 0.06 to 1.01), p<0.059). Breast-fed infants accounted for the vast majority of cases. The number receiving no prophylaxis fell consecutively over time: 20 of 27 in VKDB-90, 10 of 32 in VKDB-94 and 4 (because of parental refusal) of 7 in VKDB-02. Seven received one oral dose of VK in VKDB-90, 16 in VKDB-94 and none in VKDB-02. Underlying liver disease was found in six cases in VKDB-90, 12 in VKDB-94 and one in VKDB-02. Conclusions: In the most recent survey, the incidence of VKDB was about one third that in the two earlier studies. Late onset VKDB remains virtually confined to breast-fed infants who have received either no VK or just one oral dose. The effectiveness of oral prophylaxis regimens has improved over the last 15 years, but parental refusal of prophylaxis has become more problematic.